Pengaruh Profitabilitas, Dewan Komisaris Independen, Foreign Ownership, dan Green Accounting Terhadap Pengungkapan Sustainability Reporting - Halfi Nurhakiki; Ria Nelly Sari; Supriono (Akuntansi & Ekonomika, 2024)
This research aims to examine the influence of profitability, independent board of commissioners, foreign ownership, and green accounting on sustainability reporting disclosures in LQ45 companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Using quantitative methods with secondary. The population in this research is all LQ45 companies on the Indonesia Stock Exchange in 2018-2022, totaling 71 companies. The sample determination utilized the purposive sampling method, resulting in 37 company samples determined based on predetermined parameters over a period of 5 years so that a total of 185 data were obtained. The data analysis method used in this research is WarpPLS 8.0. The research results show that profitability, independent board of commissioners, and green accounting have an influence on sustainability reporting disclosure. Meanwhile, foreign ownership has no influence on sustainability reporting disclosures.